Performance-based comparison of Yamada–Ota and Xue models for radiative flow of dusty Ellis trihybrid nanofluid with Dufour-Soret effects - Bandar Almohsen; Munawar Abbas; Talib K. Ibrahim; Dilsora Abduvalieva; Liaqat Ali; Ansar Abbas (Advances in Mechanical Engineering)
Graphical abstract